Feminist or Paternalistic: Understanding Men’s Motivations to Confront Sexism - Estevan-Reina, Lucía; de Lemus, Soledad; Megías, Jesús L. (Frontiers in Psychology, 2020)
The role of men in fighting gender inequality is a controversial issue. Literature has shown that advantaged group members can promote social change but also perpetuate status quo. We conducted three studies to examine two motivational processes that may lead men to confront sexism: an egalitarian path and a paternalistic one. Studies 1–3 revealed that men high in benevolent sexism were more willing to confront sexism for paternalistic reasons, whereas Studies 2–3 found that men high in feminist identification were more likely to confront sexism for egalitarian reasons. Pooled analyses (Studies 1–3) supported the egalitarian and paternalistic paths underlying sexism confrontation. Moreover, Studies 2 and 3 extended these findings to collective action and engagement in the men’s activist movement that aims to reflect on male privilege (i.e the Men for Equity movement). These results highlight the existence of various underlying motivations to confront sexism by men, as well as the limits of paternalism and the potential of feminism to motivate men to take part in other kinds of actions beyond confrontation to foster social change.